Analysis of salivary proteomic biomarkers for the surveillance of changes in high-risk status of early childhood caries - Xinzhu Zhou; Haozhe Li; Ce Zhu; Chao Yuan; Chunhua Meng; Shulan Feng; Xiangyu Sun; Shuguo Zheng (BMC Oral Health, 2021)
Abstract Background Early childhood caries is an urgent public health concern. The aim of this study was to investigate salivary proteomic biomarkers for the surveillance of changes in the high-risk status of early childhood caries. The process involves the screening of specific salivary peptides that were differentially expressed only under dynamic changes in individual caries status. Methods Stimulated whole saliva samples were collected from 28 kindergarten children aged 3–4 years in Beijing at baseline and 3 months and 6 months after baseline. A total of 68 samples were collected. In terms of their caries status and progress during the observation period, participants were divided into 3 groups; 7 in the non-caries recurrence group, 6 in the caries recurrence group, and 15 in the healthy control group. Salivary peptides that exhibited no significant differences in cross-sectional comparisons between different groups of caries status but only expressed differentially along with dynamic changes of individual caries were screened using the technique of magnetic beads combined with matrix-assisted laser desorption-ionization time-of-flight mass spectrometry (MALDI-TOF MS). The technique of liquid chromatography-electrospray ionization-tandem mass spectrometry (LC-ESI-MS/MS) was employed to identify the proteins from which these peptides were derived. Results We found two salivary peptides differentially expressed only under dynamic changes in individual caries status in the above comparisons; mass-to-charge ratio (m/z) values of the two peptides were 1045.9 and 2517.6, respectively (P < 0.05). Principal component analysis (PCA) and the decision tree model based on these two peptides showed an acceptable distinguishing ability for changes in the high-risk status of early childhood caries. The source proteins of the two peptides with m/z values of 1045.9 and 2517.6 were identified as submandibular gland androgen regulatory protein 3B (SMR-3B) and mucin-7, respectively. Conclusions Two proteins in children’s saliva, namely SMR-3B and mucin-7, have the potentiality to serve as candidate biomarkers for dynamic surveillance of changes in high-risk status of early childhood caries.